2016
DOI: 10.1016/j.plabm.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Lactate point-of-care testing for acidosis: Cross-comparison of two devices with routine laboratory results

Abstract: ObjectivesLactate is a major parameter in medical decision making. During labor, it is an indicator for fetal acidosis and immediate intervention. In the Emergency Department (ED), rapid analysis of lactate/blood gas is crucial for optimal patient care. Our objectives were to cross-compare-for the first time-two point-of-care testing (POCT) lactate devices with routine laboratory results using novel tight precision targets and evaluate different lactate cut-off concentrations to predict metabolic acidosis.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The correlation and categorization of BLAC from both testing methods show that POCT can accurately measure blood lactic acid values in cancer patients. This finding is consistent with those from previous studies that have shown that a POC device can provide reliable blood lactic acid measurements in ED and delivery rooms [ 8 10 ]. The assessment of lactic acid by POCT in cancer patients can timely identify who is at risk for sepsis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The correlation and categorization of BLAC from both testing methods show that POCT can accurately measure blood lactic acid values in cancer patients. This finding is consistent with those from previous studies that have shown that a POC device can provide reliable blood lactic acid measurements in ED and delivery rooms [ 8 10 ]. The assessment of lactic acid by POCT in cancer patients can timely identify who is at risk for sepsis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that POC devices are able provide reliable measurements of lactate levels in delivery rooms and emergency departments (ED) [ 8 10 ]. In the study reported here, we shift the focus to cancer patients who not only have cells producing more lactate but may be receiving treatment making them more susceptible to systemic infections.…”
Section: Introductionmentioning
confidence: 99%
“…Bedside point-of-care lactate measurements have been shown to have excellent correlation with lab-reported lactate levels. 27 We included only the first lactate level and clinical impression obtained during any ED visit in the dataset, and for individuals with multiple ED visits during the study period, only the first lactate level and clinical impression of the most recent encounter was included. We excluded patients with a diagnosis of seizure because associated high lactate levels carry a very low mortality risk in that subset and prior lactate research studies have excluded patients with seizures 2,12 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement is based on an electrochemical reaction when lactate in whole blood reacts with the strip inserted in the SSX that 7 Feasibility of the SSX has been demonstrated in a prehospital setting, with acceptable reproducibility and concordance at clinically relevant concentrations compared to standard laboratory devices, albeit with proportional negative bias in higher concentrations. [15][16][17][18] The instrument was validated by the EMS before the study. ED physicians have access to the EMS Ambulink records where the prehospital lactate value was visible.…”
Section: Prehospital Lactatementioning
confidence: 99%